Impact of platelet pathogen inactivation on blood component utilization and patient safety in a large Austrian Regional Medical Centre. Issue 1 (21st December 2016) - Amato, M.; Schennach, H.; Astl, M.; Chen, C. Y.; Lin, J.‐S.; Benjamin, R. J.; Nussbaumer, W.
Abstract : Background: In clinical studies, pathogen inactivation (PI) of platelet concentrates (PC) with amotosalen and UVA light did not impact patient risk for haemorrhage but may affect transfusion frequency and component utilization. We evaluated the influence of platelet PI on PC, red cell concentrate (RCC) and plasma use and safety in routine practice in a large regional hospital. Study Design and Methods: Comparative effectiveness of conventional vs. PI‐treated PC was analysed during two 21‐month periods, before and after PI implementation. Results: Similar numbers of patients were transfused in the pre‐PI (control, 1797) and post‐PI (test, 1694) periods with comparable numbers of PC (8611 and 7705, respectively). The mean numbers of PC per patient transfused (4·8 vs. 4·5, P = 0·43) were not different but days of PC support (5·9 vs. 5·0, P < 0·01) decreased. Most patients received RCC (86·8% control vs. 84·8% test, P = 0·90) with similar mean numbers transfused (10·8 vs. 10·2 RCC, P = 0·22), and fewer patients (55·4% control vs. 44·7% test, P < 0·01) received less plasma units (mean 9·9 vs. 7·8, respectively, P < 0·01) in the test period. The frequencies of transfusion‐related adverse events (AE) were comparable (1·3% vs. 1·4%, P = 0·95). Analysis of haematology–oncology (522 control, 452 test), cardiac surgery (739 control, 711 test), paediatric (157 control, 130 test) and neonate (23 control, 20 test) patients revealed no increase in PC, plasma and RCC utilization, or AE. Conclusion: Component utilization and patient safety were not impacted by adoption of PI for PC. RCC use per patient was comparable, suggestive of no increase in significant bleeding.